2003
DOI: 10.1177/112067210301300302
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy of the Conjunctiva in Dry Eye Patients Establishes a Correlation between Squamous Metaplasia and Dry Eye Clinical Severity

Abstract: This is the first grading system proposed for biopsy evaluation of the ocular surface in dry eye patients. These morphological and morphometric studies alone were able, even in the earliest phases of dry eye, to detect the squamous metaplasia that progresses from the surface of the epithelium to the connective tissue. This degenerative or adaptative cellular process was characterized mainly by marked increases in the stratification, epithelial cellular size and a general loss of goblet cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 7 publications
2
25
0
3
Order By: Relevance
“…This adaptive phenomenon reflects the need for protection from external influences, or the response to proliferative stimuli from the environment. These findings agree with the findings from other authors [11,12,15,[16][17][18][19][20][21][22][24][25][26], but aging as a key factor for the appearance of dry eye syndrome was established in numerous studies [2,24,25,27,28].…”
Section: Disscusionsupporting
confidence: 83%
“…This adaptive phenomenon reflects the need for protection from external influences, or the response to proliferative stimuli from the environment. These findings agree with the findings from other authors [11,12,15,[16][17][18][19][20][21][22][24][25][26], but aging as a key factor for the appearance of dry eye syndrome was established in numerous studies [2,24,25,27,28].…”
Section: Disscusionsupporting
confidence: 83%
“…18 In this study, the epithelial cells showed morphologic and morphometric characteristics similar to those previously reported in studies that used impression cytology. 15 Impression cytology is a noninvasive method performed under local anesthesia in clinical practice with immediate results. Because it permits examination of only the most superficial epithelial layers of the ocular surface, impression cytology is an excellent diagnostic test for epithelial ocular surface, but it provides no information regarding the cornea, conjunctiva, and limbus stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Hemos realizado un estudio sobre 98 ojos de 57 pacientes (35 hombres y 22 mujeres) con insuficiencia limbal causada por diversas etiologías: quemaduras oculares (24 ojos), aniridia (22 ojos), postcirugía de pterigion u otros procesos con implicación conjuntival (12), penfigoide ocular cicatricial (10), portadores de lentes de contacto (10), síndro-me de Stevens-Johnson (6), síndrome de Lyell (4), acné rosácea (4), otros de causa desconocida (6). Mediante anamnesis y exploración se establecieron cuatro grupos clínicos dependiendo de que los pacientes no manifestaran trastornos clínicos relacionados con la deficiencia limbal (grupo 0) o estos fuesen leves (grupo 1), moderados (grupo 2) o graves (grupo 3).…”
Section: Sujetos Materials Y Métodosunclassified
“…Aunque la aplicación más común de la citología de impresión en la práctica clínica oftalmológica es valorar el grado de metaplasia escamosa conjuntival en pacientes con clínica de ojo seco (12), ésta también ha sido utilizada para valorar el grado de recuperación de la superficie corneal en pacientes tratados con trasplante de membrana amniótica o cirugía combinada de ésta con trasplante de limbo (13)(14)(15).…”
Section: Introductionunclassified